The Social Rhetoric of the Qur’an: A Thematic Stylistic Approach - Harahap, Partomuan; Asrina; Hadi, Syofyan; Nurlaila (Arabiyatuna: Jurnal Bahasa Arab, 2025)
This study explores the way the Qur’an conveys social criticism through its distinctive rhetorical style. Employing a thematic stylistic approach, the research analyzed selected verses representing criticism of social inequality (Q.S. Al-Isra’: 26–27), human and environmental exploitation (Q.S. Al-Qasas: 4; Q.S. Ar-Rum: 41), and moral deviation (Q.S. Al-Hujurat: 11; Q.S. An-Nisa’: 58). The method applied was qualitative-descriptive, using critical textual reading focusing on the thematic and stylistic features of the verses. The analysis drew on al-Sakkaki’s theory of al-Ma‘ani to identify the rhetorical forms and their social meanings. The findings indicate that in Q.S. Al-Isra’: 26–27, the Qur’an employs Uslub al-Amr as a form of ethical motivation; Uslub Khatimah Maw‘iẓiyyah to frame prohibition with theological condemnation; Uslub Siyaq wa Sibaq to balance commands and prohibitions; and Uslub Taqdīm wa Ta’khīr to emphasize social priorities in the distribution of rights. In Q.S. Al-Qasas: 4, rhetorical devices include Uslub Ta’kīd, Taqdīm wa Ta’khīr, Iṭnāb, and the use of Fiʿl Muḍāriʿ in Maqām Zamm. In Q.S. Ar-Rum: 41, the text contains Ta’kīd, causality style (‘Illah/Ta‘līl), Maqām Taḍmīn, Fiʿl Muḍāriʿ in contextual emphasis, and further Iṭnāb. In Q.S. Al-Hujurat: 11, the styles include Uslub Nidā’, Taqdīm wa Taʾkhīr, At-Tikrār, and Tahdīd. In Q.S. An-Nisa’: 58, rhetorical devices identified are Ta’kīd, Tarkīb Fiʿlī Muḍāriʿ, Kalimah Syarṭiyyah, numerical reinforcement, and Khatimah Ilahiyyah. This study introduces the concept of “Qur’anic Social Rhetoric,” a stylistic perspective that highlights the interrelation between the Qur’an’s rhetorical structures and their socio-ethical functions. It demonstrates that the Qur’anic style not only embodies aesthetic and linguistic excellence but also serves as a medium of social critique, moral guidance, and transformation, ultimately reflecting the Qur’an’s essential role in shaping public ethics and social justice.